The pilot study of the features of HIV-1 resistant variants spread using molecular clusters - Alina A. Kirichenko; Dmitry E. Kireev; Yulia N. Sidorina; Natalia D. Abashina; Elena E. Brusentseva; Vasily G. Akimkin (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. As a result of routine testing of HIV-1 drug resistance (DR), a significant amount of viral nucleotide sequences and epidemiological data of HIV-infected individuals have been collected. Combined with the increasing use of bioinformatics methods in practice, it has become possible to study the features of HIV-1 resistant variants spread using molecular clustering analysis.